The Community Reading Garden of Kasepuhan Banten Kidul: Opening Access to Reading Literacy in the 4.0 Era - Mualimah, Eka Nurul; Aryadi, Dc; Salim, Agus (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The Community Reading Garden (TBM) of Kasepuhan Banten plays an important role in enhancing the reading literacy of the community, especially in the challenging digital era. This study aims to explore the role of TBM in opening access to reading literacy in the Kasepuhan Banten region and its impact on improving the reading skills of the community in the 4.0 era. Using a qualitative approach with a descriptive method, data were collected through observations, in-depth interviews, and focus group discussions (FGD) with TBM managers and users. The findings show that TBM has successfully provided broader access to reading through physical and digital book collections, as well as utilizing technology to support literacy activities. However, there are challenges related to limited technological infrastructure, low digital skills among some members of the community, and a lack of resources for more optimal management. This study offers recommendations to enhance the role of TBM by strengthening the use of technology and providing digital training for the community to improve reading literacy in Kasepuhan Banten.